GRAPHITE, SEMI-GRAPHITE, NATURAL COKE, AND NATURAL CHAR CLASSIFICATION-ICCP SYSTEM - Kwiecińska B.; Petersen H.I. (My University, 2004)
This document presents the International Committee for Coal and Organic Petrology (ICCP) classification of four organic components that cannot be included into any of the three maceral groups vitrinite, inertinite and liptinite: (1) Graphite; (2) Semi-graphite; (3) Natural coke; and (4) Natural char. Graphite and semi-graphite are related to high metamorphic grades and can be considered as end-members of the continuous coalification process of organic matter initially deposited as peat. Natural coke is formed from coal by a relatively local elevated heat flow caused by an intrusive body and it may thus occur in a range of coalification stages. Influence of heat from fire on coal or on gelified organic matter in peat forms natural char which therefore also occurs in a wide range of coalification stages.
Keywords: Graphite; Semi-graphite; Natural coke; Natural char; Classification; ICCP